Functional Mobility Outcomes in Telehealth and In-Person Assessments for Wheeled Mobility Devices - Mitchell Bell; Richard M. Schein; Joseph Straatmann; Brad E. Dicianno; Mark R. Schmeler (International Journal of Telerehabilitation, 2020)
The purpose of this study was to compare telehealth and in-person service delivery models for wheeled mobility devices in terms of functional outcomes. We hypothesized that clinically significant improvements in functional mobility measured by the Functional Mobility Assessment (FMA) will occur in individuals receiving both telehealth and in-person clinic evaluations. A total of 27 Veterans receiving telehealth visits were compared to 27 individuals seen in clinic, selected from a database, matching for age, gender, and primary diagnosis. All mean individual item and total FMA scores in both groups increased from Time 1 to Time 2. Within the telehealth group, all changes in individual item and total FMA scores were statistically significant, with changes in 8 of 10 items meeting threshold for clinical significance (change >1.85 points). Within the clinic group, changes in 7 of 10 individual items and total FMA scores were statistically significant, and these same 7 items met threshold for clinical significance. Change scores for individual item and total FMA scores did not differ significantly between the two groups. A larger and clinically significant change in transfer score was seen in the telehealth group, suggesting telehealth visits may confer an advantage in being able to assess and address transfer issues in the home.